The Need For a Contemporary Nigerian Philosophy to be Taught at Every Level of Nigeria’s Educational Programme - Iwuagwu, Emmanuel Kelechi (European Scientific Journal, ESJ, 2016)
This paper while acknowledging the importance of an in-depth study of Western philosophy as well as African philosophy for students of philosophy department holds that this content will not bring about the ethical, socio-political and economic reengineering very much needed in Nigeria. It is the contention of this paper that there is great need for social value reorientation in Nigeria and philosophy should provide the hub for this reengineering of the Nigerian society. The paper argues that there is a big vacuum at the base of Nigeria’s educational system where the students lack any philosophical sense of direction and do not as much as know the philosophy that underlies the societal way of life. The paper employing a critical philosophical appraisal of the current state of affairs argues that philosophy should not only be merely introduced to university students as one of the general courses studied for one semester, it should be studied from the nursery/primary school level through the secondary school to the university level. The content according to this paper should be well articulated as Contemporary Nigerian Philosophy with emphasis on moral leadership training with focus to incorporate future leaders into national values as well as inculcate in them a sense of patriotism which will help address the current ethical, socio-political and economic problems confronting the present day Nigerian society. The paper concluded by advocating the philosophical formulation of a generally acceptable value design to be copied by every segment of the society which will be taught as Contemporary Nigerian Philosophy at all levels of the Nigerian educational program and for all students whether in public or private schools.